Innovating the Blue Economy: A Novel Approach to Stakeholder Landscape Mapping of the Atlantic Area Sea Basin - Depellegrin, Daniel; Zawalna-Geer, Aleksandra; Alexander, Allen; Rodeiro-Pazos, David; Dios-Vicente, Adrian; Teillant, Boris; Guneratman, Amita; Hogan, Kate; Mendonça, Emanuel; Ashton, Ian; Johanning, Lars (Frontiers in Marine Science, 2022)
The Blue Economy is an emerging paradigm with the potential to foster balanced socio-economic development of the world’s oceans and coastal areas, but it requires an understanding of the stakeholder landscape at a national and at an international sea basin scale, so that we can model potential equitable and collaborative economic development. Applying a novel, mixed-method approach we collected, collated and analysed spatial and non-spatial stakeholder information from five countries (United Kingdom, Ireland, France, Spain and Portugal), that border the North East Atlantic sea basin. Through the development of Blue Economy stakeholder directory for the North East Atlantic area more than 600 local, regional, national and international (EU wide and global) stakeholders were analysed in terms of their Blue Economy alignment and to determine their respective enabling role (financier, service providers, research/innovators and regulators/policy makers). Results show 72% of the North East Atlantic sea basin stakeholders fail to recognise the socio-economic potential of the Blue Economy, regardless of the new policy instruments and a strategic focus from the European Commission. We also identify that public and research/academic institutions currently dominate the landscape of Blue Economy stakeholders; but note this is inconsistent, when compared with other economic sectors in maritime territories. Based on the results, we discuss the key challenges facing equitable growth of the Blue Economy in the North East Atlantic area.